Interorganizational relationships between exporting companies and advising on foreing trade: a study in dyads in the furniture industry - Cislaghi, Tatiane Pellin; Larentis, Fabiano; Tondolo, Vilmar Antonio Gonçalves; Milan, Gabriel Sperandio (Revista de Administração da UFSM, 2018)
This study aimed to analyze the interorganizational relationships (IORs) between focal firms (export furniture industry) and members of support (advising on foreign trade) in the context of supply chains in the furniture industry. The study are conducted by a multiple cases in three dyads. The results indicated that with the development of IRs, the confidence gained allowed qualifying service delivery. It was identified also that the most frequent personal contact, and employees of the investigated dyads get to know personally allowed a better IOR. On the other hand, the distancing of relations caused the spacing between sectors involved and dissatisfaction on the lack of advisory services to introduce innovations.